A time-multiplexed switched-capacitor CDS equalizer with reduced crosstalk layout - Ng, K. A. (2009)
A new time-multiplexed switched-capacitor (TM-SC)equalizer is designed on the basis of the previously reported correlated double-sampling integrator and the crosstalk reduction layout approach, which aims at improving the performance aspects